In vitro antioxidant capacity of Euphorbia retusa Forssk. from Algerian desert - Selwa Lahmadi; Mohamed Belhamra; Samira Karoune; Mohamed Seif Allah Kechebar; Chawki Bensouici; Imad Kashi; Ouahiba Mizab; Riadh Ksouri (GarVal Editorial Ltda., 2019)
Context: Euphorbia retusa Forssk. is a medicinal plant, which traditionally is used in Algerian Sahara for treatment of infantile eczema, warts and trichiasis. Aims: To evaluate phenolic composition and antioxidant capacity of methanolic extracts from stems, leaves and seeds of Euphorbia retusa. Methods: Total phenolic and flavonoids were analyzed by Folin-Ciocalteu and aluminum chloride assays, respectively using gallic acid (GA) and quercetin (Q) as standard compounds. Antioxidant capacity was studied in vitro by using DPPH and ABTS cation radical scavenging, cupric-reducing antioxidant capacity (CUPRAC) and reducing power assays, followed by identification of phenolic compounds of seeds by mean of high-performance liquid chromatography (HPLC-DAD). Results: Methanolic extracts of E. retusa seeds had the highest total phenolic and flavonoid contents with 315.50 ± 1.41 µg GA equivalent/mg dry extract and 91.83 ± 8.18 µg Q equivalent/mg dry extract, respectively. Identification of phenolic compounds from seeds revealed that epigallocatechin 3-O- gallate was the major flavonoid. This organ showed the highest activity in the assays of DPPH (IC50 = 7.20 ± 0.25 µg/mL), ABTS (IC50 < 6.25 µg/mL), CUPRAC (A0.5 = 10.64 ± 0.99 µg/mL) and reducing power (A0.5 = 11.84 ± 1.72 µg/mL). Conclusions: Euphorbia retusa seeds have an antioxidant capacity that could be useful in pharmacological and medicinal fields.